Efek Annealing Pada Penumbuhan Film Tipis Ferroelektrik PbZr0,625Ti0,375O3 (PZT) - Ngurah Ayu Ketut Umiati; Irzaman Irzaman; Maman Budiman; M. Barmawi (Indonesian Journal of Physics, 2001)
Ferroelectric materials have many advantages including microactuator (piezoelectric properties), Dynamic Random Access Memory, DRAM (permitivity and polarisability) and infrared sensor (pyroelectric properties). PbZr1-xTixO3 (PZT) is ferroelectric materials, that can be piezoelectric and pyroelectric materials. In this experiment, annealing effect on growing process of thin films PbZr1-xTixO3 (PZT) using dc unbalanced magnetron sputtering is studies. PZT thin films were deposited at temperature 550oC – 650oC on Si (100) substrate with annealing condition and without annealing condition. Ratio of gas flow Ar/O2 was 50 sccm : 10 sccm, basic pressure was 0.051 Torr, and deposition pressure was 1.3 Torr. Annealing temperature was 650oC at pressure 0.58 Torr. The XRD results showed that annealing process caused crystal orientation of thin films more oddered. Some orientations that appear in the results without annealing process disappear after annealing process. This can also be seen in the morphological form of grain size PZT obtained from SEM characterization.